2017
DOI: 10.1007/s00394-017-1527-7
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity and expression profiles of genes induced by sulforaphane in human melanoma cells

Abstract: PurposeHuman melanoma is a highly aggressive incurable cancer due to intrinsic cellular resistance to apoptosis, reprogramming, proliferation and survival during tumour progression. Sulforaphane (SFN), an isothiocyanate found in cruciferous vegetables, plays a role in carcinogenesis in many cancer types. However, the cytotoxic molecular mechanisms and gene expression profiles promoted by SFN in human melanoma remain unknown.MethodsThree different cell lines were used: two human melanoma A375 and 501MEL and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 77 publications
4
24
0
Order By: Relevance
“…EGR1 exhibits a dual role of a tumor suppressor or a tumor-promoting factor in various carcinomas, by regulating cell cycle progression, apoptosis and malignant transformations (19)(20)(21). EGR1 stimulates cells proliferation in prostate, stomach, and kidney cancer (22)(23)(24), whereas it shows a tumor-suppressive activity in breast cancer, melanoma, fibrosarcoma and B cell lymphoma (25)(26)(27)(28). Our results also indicate a tumor-suppressive activity of EGR1 in CTCL.…”
Section: Discussionsupporting
confidence: 63%
“…EGR1 exhibits a dual role of a tumor suppressor or a tumor-promoting factor in various carcinomas, by regulating cell cycle progression, apoptosis and malignant transformations (19)(20)(21). EGR1 stimulates cells proliferation in prostate, stomach, and kidney cancer (22)(23)(24), whereas it shows a tumor-suppressive activity in breast cancer, melanoma, fibrosarcoma and B cell lymphoma (25)(26)(27)(28). Our results also indicate a tumor-suppressive activity of EGR1 in CTCL.…”
Section: Discussionsupporting
confidence: 63%
“…This result is different from that in leukemia cells , in which there was no significant change in total protein level of P53 from 24 to 48 h in 6‐MSITC‐treated cells. On the other hand, treatment with sulforaphane, an analog of 6‐MSITC, also increased the expression level of P53 in prostate cancer cells and melanoma cells , but not in leukemia cells . Therefore, the effects of 6‐MSITC on the protein level of P53 might depend on the cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SFN increases the percentage of apoptotic melanoma cells by cleaving poly (ADP-ribose) polymerase (PARP), activating p-p53, caspase-3, caspase-8, and caspase-9, and decreasing Bcl2 expression, thus confirming its pro-apoptotic role. SFN is a very attractive multipotent anti-cancer agent, and its use could open new avenues for preventing tumor growth and treating human malignancies [58]. Sulforaphanes as well as other phytocompounds (e.g., curcumin, epigallocatechin gallate (EGCG), resveratrol, lycopene, SR-T100, several flavonoids, wogonin, Wisteria floribunda agglutinin (WFA), ginsenosides, and genistein derivatives) have been demonstrated to reduce CSC-related marker levels and inhibit CSC-related signaling pathways in ovarian cancer, suggesting their potential use to overcome its chemoresistance and relapse, mainly due to the CSC fraction [76].…”
Section: Itc Anti-cancer Activity In Different Tumorsmentioning
confidence: 99%